The history of equal suffrage in Colorado, 1868-1898 - Brown, J. G. (Joseph G.), 1844-; Stone, Lucy, 1818-1893; National American Woman Suffrage Association Collection (Library of Congress) (Denver, Colo., News job printing co., 1898)
Colorado women were enfranchised in 1898. This book details the history of that struggle. It includes a discussion of the growth of Colorado women's clubs as an important factor in the campaign. It also provides lists of suffrage workers and of women who have been elected and appointed to positions in Colorado government in the late nineteenth century.
Also available in digital form on the Library of Congress Web site.
Keywords: Women -- Suffrage -- Colorado; Women -- Political activity -- Colorado